Relatório de estágio supervisionado na área de tecnologia e inspeção de alimentos e relato de caso sobre a percepção dos manipuladores de alimentos quanto às boas práticas de fabricação em panificadora - Lima, Ana Maria de Assunção (Universidade Federal Rural do Semi-Árido, 2020)
The demand for safe foods is growing and has been generating ever greater demands in relation to the hygienic-sanitary conditions in which these foods are produced. The current legislation makes the use of Good Manufacturing Practices (GMP) mandatory for all food industries and services, including bakeries, which present several problems related to the hygienic-sanitary conditions of production sites and food handlers. The manipulator's lack of knowledge or neglect of these good practices can result in food contamination. Thus, the present study aimed to practice activities related to the inspection routine during the preparation and handling of food, as well as to evaluate the knowledge of the bakers' handlers about GMP and their conduct during food handling, since the adoption of these practices is fundamental to guarantee the hygienic-sanitary quality of the food. During the internship period, it was possible to monitor the routine activities of the technician responsible, the production process of different products, among other activities. Data were collected by applying a questionnaire after signing the Free and Informed Consent Form. The questionnaire was divided into five parts, which included identification and professional profile; GMP; personal, environmental and food handling hygiene. There were four volunteers, three bakers and a baker assistant. All were men, with a prevalent age group between 21-30 years and 50% had incomplete high school. All handlers had access to knowledge about GMP through courses or training, with 75% considering GMP as very important. However, they had difficulties in identifying the items that could contaminate food. As for self-declared behavior in relation to personal hygiene and environmental hygiene, they demonstrated to act in accordance with current legislation. The same did not happen with hygiene during food handling. The internship allowed expanding and improving theoretical and practical knowledge in the area oftechnology and food inspection. It is essential that training on GMP be carried out properly and continuously, as well as it is important to monitor the manipulators during their activities.
Keywords: Segurança dos alimentos; Manipulação de alimentos; Qualidade higiênico sanitária; Food safety; Food handling; Hygienic-sanitary quality; CIENCIAS AGRARIAS::MEDICINA VETERINARIA